Existence and psychotherapy - Błaszczyk, Marek (Hybris, 2022)
The article presents a critical approach to Pasaże egzystencji. Strony psychoterapii i inne strony by Małgorzata Opoczyńska (Wydawnictwo Uniwersytetu Jagiellońskiego, Kraków 2019). It discusses the main theses presented in the dissertation and invites to a multifaceted, philosophical and psychological reflection on the problem of human existence.